Tuftsin-tailored fusion protein inhibits the growth of circulating gastric tumor cells associated with macrophage phagocytosis - Dandan Yuan; Xiaoyang Zhai; Kunli Zhu; Jiangang Ji; Wenjuan Liu (Biochemistry and Biophysics Reports, 2023)
Circulating tumor cells (CTCs) are a major cause of tumor metastasis and resistance to anticancer therapies. To date, no effective low-toxicity chemotherapeutic agents or antibodies have exhibited significant clinical activity against CTCs. Macrophages are important mediators of antitumor immunity. Tuftsin (TF), a tetrapeptide located at residues 289–292 of the CH2 domain of the Fc region of the IgG heavy chain, binds to Nrp-1, a receptor on the surface of macrophages that promotes phagocytosis and induces nonspecific activation of the immune system against tumors. Lidamycin (LDM) is an antitumor chemotherapy agent that is strongly cytotoxic to tumors and can dissociate into an apoprotein (LDP) and active enediyne (AE) in vitro. We previously constructed the fusion protein LDP-TF through genetic engineering and inserted the chromophore AE to produce LDM-TF, which can target macrophages to promote their phagocytic and cytotoxic activity against tumor cells. Preliminary experiments confirmed the anti-tumor activity of LDM-TFs. In this study, we found that LDM-TF effectively inhibited the growth of CTCs of gastric cancer origin and enhanced macrophage phagocytosis both in vivo and in vitro. Tumor cell expression of CD47, which helps to evade phagocytosis by macrophages, was substantially downregulated by LDM-TF. Notably, our in vitro experiments demonstrated that the combination of LDM-TF and anti-CD47 antibodies promoted phagocytosis more than either component alone. Our findings demonstrate the significant inhibitory effect of LDM-TF on the growth of CTCs of gastric cancer origin and suggest that the combination of LDM-TF and anti-CD47 antibodies may exhibit synergistic effects, thereby providing a new option for the clinical treatment of patients with advanced tumors that have metastasized.